(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
This article deals with the lexical-semantic and linguocultural study of terms in English and Uzbek. Based on the analysis of educational, lexicographic and reference sources, five groups of polysemantic sports terms have been identified. Uzbek-language correspondences of English-language terms that have different meanings in different sports and in one sport are presented. The influence of the context on the choice of translation variant is demonstrated.